2017
DOI: 10.3727/096504016x14816726393937
|View full text |Cite
|
Sign up to set email alerts
|

GGNBP2 Suppresses the Proliferation, Invasion, and Migration of Human Glioma Cells

Abstract: Gliomas are the most common and aggressive type of primary adult brain tumors. Although GGNBP2 has previously been considered to be a tumor suppressor gene, little is known about the association between GGNBP2 and glioma. In this study, we clearly demonstrated that GGNBP2 was downexpressed in glioma tissues, and its downexpression is related to the pathological grade and overall survival of patients with gliomas. Overexpression of GGNBP2 suppressed the proliferation, migration, and invasion of glioma cells. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…Prostate cancer is the most common malignant tumour in men of developed countries and the second leading cause for death among male cancer patients. GGNBP2 is located in the human chromosome 17q12‐21.1 region, and the genes encoded in this region are closely related to the progression of breast cancer (Yang et al, ), ovarian cancer (May et al, ), laryngeal cancer (Chen et al, ) and glioma (Zhan et al, ). In tumour cells, the normal processes of gene transcription and cleavage are disrupted, and abnormal mutations in genes and disorders in transcription and translation processes can lead to the synthesis of mRNA that does not exist originally, or the proportion of transcription or translation of different cuts.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is the most common malignant tumour in men of developed countries and the second leading cause for death among male cancer patients. GGNBP2 is located in the human chromosome 17q12‐21.1 region, and the genes encoded in this region are closely related to the progression of breast cancer (Yang et al, ), ovarian cancer (May et al, ), laryngeal cancer (Chen et al, ) and glioma (Zhan et al, ). In tumour cells, the normal processes of gene transcription and cleavage are disrupted, and abnormal mutations in genes and disorders in transcription and translation processes can lead to the synthesis of mRNA that does not exist originally, or the proportion of transcription or translation of different cuts.…”
Section: Discussionmentioning
confidence: 99%
“…ZFP403 is closely associated with the occurrence and development of several types of cancer ( 13 ). Studies have demonstrated that full-length ZFP403 may serve as a potential tumor suppressor, and that ZFP403 is downregulated in various malignant tumors, such as breast ( 9 ), ovarian cancer ( 14 ) and glioma ( 15 ). Furthermore, the absence of ZFP403 can promote cellular proliferation ( 16 ) and tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, overexpression of GGNBP2 suppresses tumor proliferation and metastasis and its down-regulation is associated with drug resistance in ovarian cancer [11,12]. In glioma, GGNBP2 also functions a tumor suppressor [13]. However, some studies indicate that depletion of GGNBP2 leads to cell cycle arrest at G2/M phase and inhibition of cell proliferation, suggesting that GGNBP2 may also function as an oncogene [14].…”
Section: Introductionmentioning
confidence: 99%